Report on the Pacific Roundtables : Actions to Address Correspondent Banking and Remittances Pressure - Stuart, Alison (Departmental Papers; Departmental Paper, 2019)
The paper looks at feasible concrete action that can be taken by correspondent and respondent banks, money transfer operators, the Pacific authorities, the Australian and New Zealand authorities, and international organizations.